KLAUSULA BAKU DAN TANGGUNG JAWAB PEMERINTAH DALAM RANGKA PERLINDUNGAN KONSUMEN PADA PERDAGANGAN SECARA ELEKTRONIK - Yuli Heriyanti; Ahmad Zikri; Miswar (Pahlawan Tuanku Tambusai University, 2023)
Humans present on earth have actually been equipped with knowledge by the creator. The knowledge that humans get is used as a helping tool for survival. Electronic commerce requires business actors to innovate and be creative so that consumers are interested in shopping at their online shop. In addition, electronic trading also requires business actors to make rules and conditions that apply to legally bind and protect such trade. The rules that are made should be able to bind the parties carrying out e-commerce. What needs to be known is that engagements that occur in e-commerce are not only between business actors/producers, but also consumers and other parties who act as senders of goods known as expeditions. The development of online trading/e-commerce requires that business actors also apply applicable rules in order to protect the rights and obligations of the parties in electronic trading or e-commerce. Keywords: Consumer Protection, Electronic Trading